Gambaran Persepsi Remaja Terhadap Aplikasi Tiktok : Sebuah Studi Fenomenologi Interpretatif - Ramadhani, Jihan (Happiness: Journal of Psychology and Islamic Science, 2021)
This studi aims to determine the description of adolescent perceptions of tiktok applications. The study was conducted using a qualitative approach with phenomenological methods. Then to determine informants using purposive sampling technique, with certain considerations, namely adolescents in Payakumbuh who have the Tiktok application and actively use it. Through semi-structural interviews, data were collected from each subject, all series of interviews conducted were recorded and then transcribed. The results of this study found that there were three identified themes, namely positive impact, negatif impacts and factors thay influenced participants in using the Tiktok application.